First-principles investigation of structural, electronic, and optical properties of cubic halide perovskite RbSrI3 - G Ajay; M Mohamed Sheik Sirajuddeen; V Ashwin (Chemical Physics Impact, 2024)
In this article, the structural, electronic, and optical properties of lead-free cubic halide perovskite RbSrI3 are investigated by the first principles method that employs the density functional theory (DFT). This study implements the full potential linearized augmented plane wave (FP-LAPW) method with the generalized gradient approximation of Perdew-Burke-Ernzerhof (PBE-GGA) as the exchange-correlation potential. The structural stability of the compound is calculated using the Murnaghan equation of state, and the band structure calculations show the presence of a wide indirect bandgap of 3.32 eV. The optical response of the compound over the energy spectrum of 0–12 eV is studied and the compound exhibits good reflectance of 30.73 % at 7.66 eV and absorption of 112.45 × 104 cm−1 at 11.74 eV in the ultraviolet region. The values of reflectivity R(ω) and absorption coefficient α(ω) indicate that the compound shows potential in the fabrication of UV-related optoelectronic devices.